2014
DOI: 10.1111/mmi.12889
|View full text |Cite
|
Sign up to set email alerts
|

A copper‐induced quinone degradation pathway provides protection against combined copper/quinone stress in Lactococcus lactisIL1403

Abstract: SummaryQuinones are ubiquitous in the environment. They occur naturally but are also in widespread use in human and industrial activities. Quinones alone are relatively benign to bacteria, but in combination with copper, they become toxic by a mechanism that leads to intracellular thiol depletion. Here, it was shown that the yahCD-yaiAB operon of Lactococcus lactis IL1403 provides resistance to combined copper/quinone stress. The operon is under the control of CopR, which also regulates expression of the copRZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
(111 reference statements)
1
11
0
Order By: Relevance
“…Both toxicity mechanisms, however, are independent of ROS production. The lack of oxidative damage under copper stress has been documented for L. lactis (42). Copper reduced the metabolic heat flow at any phase of culture growth and delayed the attainment of maximal metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Both toxicity mechanisms, however, are independent of ROS production. The lack of oxidative damage under copper stress has been documented for L. lactis (42). Copper reduced the metabolic heat flow at any phase of culture growth and delayed the attainment of maximal metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, resistance against copper is most often dependent upon efflux mechanism. Mancini et al (2015) reported that P-type ATPases detoxify copper via efflux mechanism in some species. However, it has been reported that copper metabolism occurs naturally in all living organisms, and is generally chromosomally encoded (Ahemad 2012).…”
Section: Determination Of the Mic Of Heavy Metals And Antibiotic Resimentioning
confidence: 99%
“…These results show that the accumulation amount of metal ions by the Micrococcus strain is relatively stable for the three heavy metals and are relatively far from ours. Beside that, some studies reported that bacteria are able to accumulate and compartmentalize copper in the cell's periplasm and the outer membrane and concluded the protective mechanism against copper due to productions of four proteins to overcome copper stress (Cooksey 1994;Mancini et al 2015). Adebisi Musbaudeen et al (2014) reported that Micrococcus luteus is not only resistant against copper and nickel, but also had the extensive capability of accumulating these heavy metals.…”
Section: Accumulation Of Metal Ions By Living Bacterial Cellsmentioning
confidence: 99%
“…The experiment was performed at 25 °C in a 5 mL chamber containing 4 mL of 100 mM PBS at pH 8.0, 0.4 mL substrate (2,6-DTBP), and 0.4 mL crude protein extract. 36,37 …”
Section: Methodsmentioning
confidence: 99%